Respon Penambahan Pupuk Hayati terhadap Pertumbuhan dan Hasil Padi Sawah - Jumakir Jumakir; Endrizal Endrizal (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Jumakir J, Endrizal E. 2019.Â Response of biological fertilizer addition to growth and results of rice field.Â Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):173-180.Â The research objectives were to determine the effect or response of the addition of biological fertilizers to the growth and yield of rice, to determine the most effective type of biological fertilizer. This study was conducted in irrigated rice field of Sri Agung Village, Batang Asam sub District, West Tanjung Jabung District, Jambi Province in dry season 2016. The design was Randomized Block Design (RBD) with six treatments and three replications with 5 mx 10 m plot area, implemented in a farmer area of 1200 m2. The results of the analysis based on the analysis of variance showed significant and unreal differences in growth and yield of rice. The addition of biological fertilizer provided higher growth and yields than without biological fertilizer. Provibio biofertilizer is the most effective biofertilizer that can provide the highest rice yield and the use of biofertilizer can save 50% recommended NPK fertilizer.